2006
DOI: 10.1080/01926230500519816
|View full text |Cite
|
Sign up to set email alerts
|

Serum Chemical Biomarkers of Cardiac Injury for Nonclinical Safety Testing

Abstract: There has been a substantial increase in the number and efficacy of laboratory biomarkers for the evaluation of human cardiac injury over the last decade. The advantages of these over traditional laboratory tests have encouraged adoption of comparable markers in nonclinical studies for cardiac injury assessment. Of particular interest are markers that are not only more sensitive and/or specific than traditional parameters for cardiac injury, but also those that may directly bridge human and laboratory animal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 99 publications
4
61
0
Order By: Relevance
“…There was also no significant difference in the LD 1 /LD 2 ratio between the two groups in this study. For most, LD 5 predominates in skeletal muscle and the liver 47 , and it increased in serum in patients with non-traumatic acute rhabdomyolysis 49 . In this study, there was no significant difference in LD 5 between the two groups, and there was no indication that CLA intake inhibited leaking of LD 5 from skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also no significant difference in the LD 1 /LD 2 ratio between the two groups in this study. For most, LD 5 predominates in skeletal muscle and the liver 47 , and it increased in serum in patients with non-traumatic acute rhabdomyolysis 49 . In this study, there was no significant difference in LD 5 between the two groups, and there was no indication that CLA intake inhibited leaking of LD 5 from skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…LD 1 and LD 2 are cardiacpredominant isozymes. Increase of these isozymes in serum is considered generally supportive of myocardial injury 47 . Huang et al 48 reported that endurance training accelerates exhaustive exercise-induced apoptosis in left ventricles of rats, as a result of exhaustive running tests on a treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…Apple 1999) and preclinical research (e.g. Walker 2006). In our study, the myocardial specificity of cTnI was proven by the significant differences in the concentrations of cTnI between ISO animals and control animals at several time intervals (2, 4, 6, and 24 h).…”
Section: Discussionmentioning
confidence: 99%
“…However, after 24 h of reperfusion only very low levels of CK-MM were measured, as CK-MM is a marker of early detection of muscle injury and has a serum half-life of only about one hour in rats. 23 Additionally, we looked at the plasma level of PDGF-bb, which is known to have angiogenic effects, regulates the tonus of blood vessels and is involved in wound healing. 24,25 At low levels PDGF-bb is expressed in the endothelium, platelets and macrophages, which increases following mechanical injury and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%